21o-16p+3p+11p-9o=

Simple and best practice solution for 21o-16p+3p+11p-9o= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21o-16p+3p+11p-9o= equation:


Simplifying
21o + -16p + 3p + 11p + -9o = 0

Reorder the terms:
21o + -9o + -16p + 3p + 11p = 0

Combine like terms: 21o + -9o = 12o
12o + -16p + 3p + 11p = 0

Combine like terms: -16p + 3p = -13p
12o + -13p + 11p = 0

Combine like terms: -13p + 11p = -2p
12o + -2p = 0

Solving
12o + -2p = 0

Solving for variable 'o'.

Move all terms containing o to the left, all other terms to the right.

Add '2p' to each side of the equation.
12o + -2p + 2p = 0 + 2p

Combine like terms: -2p + 2p = 0
12o + 0 = 0 + 2p
12o = 0 + 2p
Remove the zero:
12o = 2p

Divide each side by '12'.
o = 0.1666666667p

Simplifying
o = 0.1666666667p

See similar equations:

| 16v^2+8v+1=0 | | 12+9a-6a+7a-15a+5a= | | 2x(x-3)=43 | | x^2-18x+50=0 | | 2x^2+6=8 | | -8y+6y-4y-13y= | | 4(3x+2)+2(5x-6)=5(2x+4) | | -4m+6=9m+31 | | -9b+6b-11b-3b= | | V^2-400=0 | | 10x+8-4+5x= | | 2(7x-3)+4=40 | | 14y+8=-5y+4 | | (-11a-8b)(-5a-6b)= | | -2x+15=9 | | -8-23=-15 | | 4.8x-4=3.8x | | 5x-(2x+6)=15 | | .34(y+3)=4y | | (9c-2d)(3c-7d)= | | y+3=12y | | 5v^2-19v=4 | | (6x-y)(4x+3y)= | | n^2+5=-6n | | y^2-24x+144=0 | | 2x-11=-7 | | 2a+4b+-2a+-b= | | (-z+2.1)(3z+3)= | | .50-x+1.5=x-4 | | 6x+32=80 | | (12c+5)(-6c-2)= | | 3+y=10(y+1) |

Equations solver categories